Sensitive chromogenic method development and validation for the estimation of Vitamin A in the Food and Cosmetics Products - Sri, K. Bhavya; Manusha, G.; Vallakeerthi, Narmada; Sadhula, Anitha; Kumar, V. Kiran; Sumakanth, M. (Journal of Neonatal Surgery, 2025)
Vitamin A which is Retinol Acetate this is simple ,rapid, Quantifying method of vitamin A of different products to make reacting with MBTH reagent at a cold temperature to produce a colored complex which is the basis of an easy-to use and highly sensitive UV-visible spectroscopic approach for the measurement of Vitamin. For colorimetric drug assessment, MBTH Reagent is a chromogenic reagent that contains active methylene groups, phenolic, aromatic amines, and hydroxyl groups. To determine the linearity, precision, robustness, robustness, limit of detection, and limit of quantification, validation was done. A simple, rapid, sensitive methods are used for the determination of Retinol acetate that is added in the food products by using UV-Visible spectroscopy. The method is developed by using chromogenic method (MBTH reagent) according to the ICH Q2(R2) guidelines and With an excellent correlation value (r2) of 0.9988, linear responses were observed in the range of concentrations of 20 µg/ml to 360 µg/ml. The LOD and LOQ were determined at 0.40788 μg/mL & 1.236 µg/ml, respectively.The precision (%RSD ≤ 2) found to be in acceptable limits. The chromogenic method were developed and validated which was extended to food samples that contain high amount of Vitamin A and Quantification of them in food samples